Mismatch Between Risk and Response May Amplify Lethal and Non-lethal Effects of Humans on Wild Animal Populations - Smith, Justine A.; Gaynor, Kaitlyn M.; Suraci, Justin P. (Frontiers in Ecology and Evolution, 2021)
Human activity has rapidly transformed the planet, leading to declines of animal populations around the world through a range of direct and indirect pathways. Humans have strong numerical effects on wild animal populations, as highly efficient hunters and through unintentional impacts of human activity and development. Human disturbance also induces costly non-lethal effects by changing the behavior of risk-averse animals. Here, we suggest that the unique strength of these lethal and non-lethal effects is amplified by mismatches between the nature of risk associated with anthropogenic stimuli and the corresponding response by wild animals. We discuss the unique characteristics of cues associated with anthropogenic stimuli in the context of animal ecology and evolutionary history to explore why and when animals fail to appropriately a) detect, b) assess, and c) respond to both benign and lethal stimuli. We then explore the costs of over-response to a benign stimulus (Type I error) and under-response to a lethal stimulus (Type II error), which can scale up to affect individual fitness and ultimately drive population dynamics and shape ecological interactions. Finally, we highlight avenues for future research and discuss conservation measures that can better align animal perception and response with risk to mitigate unintended consequences of human disturbance.